2011
DOI: 10.1007/s11426-011-4385-9
|View full text |Cite
|
Sign up to set email alerts
|

Principle of nonlinear chemical fingerprint by using dissipative components in samples as well as calculation and evaluation of similarity

Abstract: Under the conditions of constant temperature and pressure, different influences of samples with different chemical components on the mechanism of nonlinear chemical reaction will cause different changes of the potential-time relationship curve of the nonlinear chemical reaction system. Using it as the character, and using the B-Z nonlinear chemical system to use acetone and substrates in samples as main dissipative substances qua an example, the principle of nonlinear chemical fingerprint has been researched a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…(5) Effect of temperature According to "Procedure" Section 2.2, the nonlinear chemical fingerprints of solid Kafu fruit drink with grape flavor (1.0000g) were determined at 27,30,35,37,40,45,47, 50 and 55 °C, respectively ( Figure 4). It is obvious from the figure that the fingerprint shape and the quantitative information are very sensitive to the temperature change.…”
Section: Nonlinear Chemical Fingerprint and Its Determining Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…(5) Effect of temperature According to "Procedure" Section 2.2, the nonlinear chemical fingerprints of solid Kafu fruit drink with grape flavor (1.0000g) were determined at 27,30,35,37,40,45,47, 50 and 55 °C, respectively ( Figure 4). It is obvious from the figure that the fingerprint shape and the quantitative information are very sensitive to the temperature change.…”
Section: Nonlinear Chemical Fingerprint and Its Determining Conditionsmentioning
confidence: 99%
“…The parallel determination of identical sample was carried out with the analytical instrument of nonlinear chemical fingerprint under the optimum conditions, and the results showed that the fingerprint was of very good reproducibility; because of the differences in the components and their contents of different sorts of samples, both of the indexes of the quantifiable information and intuitionistic shapes of the inductive curve, undulatory curve and period waves in the relevant fingerprint are partly or wholly different, that is, the differences in the internal components and their contents of different samples may be revealed by the nonlinear chemical fingerprint, so the fingerprint is of the qualitative functions to the sample and the relative quantitative functions to the total content of the components [38,45]. Therefore, the abundance of the quantifiable and intuitionistic information, namely the characteristic parameters and shapes of the nonlinear chemical fingerprint may be used to evaluate quality of the sample and identify its authenticity.…”
Section: Applications Of Nonlinear Chemical Fingerprintmentioning
confidence: 99%
See 3 more Smart Citations